2021
DOI: 10.1097/md.0000000000027481
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fetuin-A and coronary atherosclerotic heart disease (CHD) and CHD-related risk factors

Abstract: Fetuin-A plays an important role in antivascular calcification and inflammatory response, it is necessary to explore the relationship between fetuin-A and coronary atherosclerotic heart disease (CHD) and CHD-related risk factors.A total of 92 patients with CHD as the research group, and 60 healthy persons as the control group were enrolled from May 2019 to May 2020. Fetuin-A levels were determined by enzyme-linked immunosorbent assay, and the characteristics and clinical data were collected and compared. Logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Fetuin-A is an endogenous protein, and its beneficial effects in different disease states are mainly attributed to suppression of pro-inflammatory cytokines release from the endotoxemia-stimulated macrophages. 25,58,59 The studies have shown an inverse relationship between the circulating Fetuin-A levels and inflammatory cytokines including IL-1 β, TNF-α, and IL-6. 60 Furthermore, it has also been reported that fetuin-A supplementation significantly inhibits the IFN-ℽ and endotoxin-induced HMGB1 (late mediator) release in a concentration-dependent manner by stimulating macrophages-mediated phagocytic elimination of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetuin-A is an endogenous protein, and its beneficial effects in different disease states are mainly attributed to suppression of pro-inflammatory cytokines release from the endotoxemia-stimulated macrophages. 25,58,59 The studies have shown an inverse relationship between the circulating Fetuin-A levels and inflammatory cytokines including IL-1 β, TNF-α, and IL-6. 60 Furthermore, it has also been reported that fetuin-A supplementation significantly inhibits the IFN-ℽ and endotoxin-induced HMGB1 (late mediator) release in a concentration-dependent manner by stimulating macrophages-mediated phagocytic elimination of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] An essential role for fetuin-A in attenuating injury and infection-elicited inflammatory responses has been well described. 25,26 Studies have shown that fetuin-A at high concentration remarkably inhibits endotoxin-induced release of proinflammatory mediators, that is, TNF, IL-1, and nitric oxide in macrophage cultures, signifying anti-inflammatory potential of fetuin-A. 24,27 In an animal model of carrageenan-induced paw edema, intraperitoneal administration of fetuin-A also attenuated local TNF production and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] The incidence of ISR after stent implantation in patients with a history of smoking and drinking is reportedly twice as high as that in those without such a history. [ 18 ] Smoking and drinking can cause coronary artery spasms and vascular endothelial cell damage, leading to atherosclerosis and platelet adhesion. Increased fibrinogen levels can further lead to thrombosis, which increases the risk of long-term mortality in patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcome of our study was 2-year worsening PAD, defined as an ABI drop greater than or equal to 0.15, as previously studies have demonstrated that this threshold is clinically relevant for limb prognosis ( 31 33 ). Given that the 5 proposed proteins have been heavily investigated for cardiac and cerebrovascular events previously ( 12 , 15 , 24 , 34 , 35 ), we aimed to specifically assess their predictive value for limb- and PAD-related outcomes. To reduce the risk of confounding from cardiovascular events, we excluded patients with acute coronary syndrome within the past 3 months to ensure that our proteins were specifically associated with PAD-related adverse events.…”
Section: Methodsmentioning
confidence: 99%